Frame analysis of safety terminology in English and Russian languages - Vekovischeva, S.N.; Priorova, E.M.; Savchenko, E.P.; Romanov, V.M. (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2017)
The paper is devoted to studying frame formation of the terminological system “Safety” from the standpoint of cognitive linguistics, its methods and tools as well as the frame simulations of the English terminology. We describe the concept of frame, the frame approach to researching terminology, a substantial invariant of the frame, main macrocategories, subframes and slots. We also present the frame scheme of English and Russian terminology of “Safety.”